SUBTITILING STRATEGIS IN COMEDY ACTION MOVIE CAN ANALYSIS OF ENGLISH INDONESIA LANGUAGE SUBTITLING OF KUNG FU PANDA - Helena.R Silaen, - (2008)
This research is entitled Subtitling Strategies in comedy action movie (An Analysis of English Indonesia subtitling of Kung Fu Panda Movie). The study was aimed to find out the strategies employed in the film. This study employed descriptive qualitative method in analyzing the data collected. The collected data then were analyzed based on the subtitling strategy drawn from Gottlieb (1998). In analyzing the data, there were several steps conducted. First making transcription. Second, analyzing each dialogue and the subtitle to discover the subtitling strategy. Finally. All subtitles can be clustered and quantified by the same types of strategies. The finding of the study showed that from 100 samples random the subtitling strategies used expansion (6.06%), paraphrase (5.05%), transfer (64.65%), imitation (2.02%), transcription (2.02%), decimation (2.02%), deletion (15.15%), and resignation (3.03%) The finding of this research are expected to give some fruitful ideas for further study in this topic and to make some contribution to the work of translation.